The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/tc-2017-117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The color of melt ponds on Arctic sea ice

Abstract: Abstract.Pond color, which creates the visual appearance of melt ponds on Arctic sea ice in summer, is quantitatively investigated in this study. A two-stream radiative transfer model is used for ponded sea ice: the upwelling irradiance from the pond surface is determined, and then the upwelling spectrum is transformed into the RGB color space through a 10 colorimetric method. The dependence of pond color on various factors such as water and ice properties and incident solar radiation is investigated. The resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The mean incident solar irradiance F 0 ( λ ) under overcast sky conditions at noon in August, where the solar disk was not visible (Grenfell & Perovich, ), is employed to represent Arctic summer. A sensitivity study on F 0 is ignored here because model simulations showed that variations in melt‐pond albedo and transmittance due to different values of F 0 are less than 3%, similar with the results in Lu et al () and Lu, Leppäranta, et al (). However, the spectral distribution rather than the absolute value of F 0 ( λ ) is needed when calculating the AOPs.…”
Section: Model Setupsupporting
confidence: 81%
See 4 more Smart Citations
“…The mean incident solar irradiance F 0 ( λ ) under overcast sky conditions at noon in August, where the solar disk was not visible (Grenfell & Perovich, ), is employed to represent Arctic summer. A sensitivity study on F 0 is ignored here because model simulations showed that variations in melt‐pond albedo and transmittance due to different values of F 0 are less than 3%, similar with the results in Lu et al () and Lu, Leppäranta, et al (). However, the spectral distribution rather than the absolute value of F 0 ( λ ) is needed when calculating the AOPs.…”
Section: Model Setupsupporting
confidence: 81%
“…Pond color, as sensed by human eyes, is another visual characterization of melt ponds in addition to their albedo. A colorimetric method to determine the color of a melt pond has been developed by Lu, Leppäranta, et al (), which transforms the upwelling spectral irradiance from the pond surface into red, green, and blue intensities in the RGB color space using color matching functions (Hunt, ), so that the melt‐pond color can be quantitatively evaluated. In this part of the analysis, the thickness and scattering coefficient of the ice lid are altered to examine the RGB color of refreezing melt ponds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations